Nonlinear dynamics of a bladed dual-shaft - Gruin, Marion; Thouverez, Fabrice; Blanc, Laurent; Jean, Pierrick (European Journal of Computational Mechanics, 2011)
In the industrial context of performance improvement of dual-shaft aircraft engines, experimental results demonstrate how important it is to consider the influence of the dynamics of the high pressure (HP) shaft on the response of the bladed disk located on the low pressure (LP) shaft. Indeed, this coupling seems to play an important role in the design purposes in rotating machinery industry as it can have a significant impact on the dynamic behaviour of turbomachines. The model developed here consists of a HP shaft and a LP bladed shaft connected by an intershaft bearing. Nonlinear features of this intershaft bearing require the development of specific nonlinear algorithms. Thus, this paper aims at coupling the two modelling levels in order to grasp the nonlinear vibratory phenomena of a bladed dual-shaft under unbalances.